Pokrajina projektov - spremembe v okviru planerske prakse na Nizozemskem - Reijndorp, Arnold (Urbani izziv, 1997)
Recently a map was presented on which all the 2650 town planning projects in the Netherlands are shown that will be realized before the year 2005 or shortly after. In this contribution the focus is on changes in the context of the profession of the urban planner as witnessed on the New map. This will give a more clear view on the changing demands from the profession and the education of urban planners are confronted with.
Keywords: Nizozemska; prostorsko planiranje; regionalni razvoj; regionalno planiranje; spatial planning; urbana sociologija; urbanism; urbanizem